2022
DOI: 10.1038/s41391-022-00498-6
|View full text |Cite
|
Sign up to set email alerts
|

Significant changes in macrophage and CD8 T cell densities in primary prostate tumors 2 weeks after SBRT

Abstract: Background Radiotherapy impacts the local immune response to cancers. Prostate Stereotactic Body Radiotherapy (SBRT) is a highly focused method to deliver radiotherapy often used to treat prostate cancer. This is the first direct comparison of immune cells within prostate cancers before and after SBRT in patients. Methods Prostate cancers before and 2 weeks after SBRT are interrogated by multiplex immune fluorescence targeting various T cells and macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Recently, a study reports that prostate stereotactic body radiotherapy (SBRT), a neoadjuvant method to radical prostatectomy, amazedly alters the immune microenvironment within PCa. Multiplex immune-fluorescence (mIF) determines the increase of CD163 + macrophage subsets in densities and reaches a 5.61-fold change 2 weeks after SBRT [ 40 ]. M1-type polarization is experimentally induced in vitro using exogenous toll-like receptor agonist, IFN- γ or combined with LPS, whereas the most potent M2-type is attained upon Th2 cytokine (like IL-4 and IL-13) stimuli [ 41 ].…”
Section: Macrophage Polarizationmentioning
confidence: 99%
“…Recently, a study reports that prostate stereotactic body radiotherapy (SBRT), a neoadjuvant method to radical prostatectomy, amazedly alters the immune microenvironment within PCa. Multiplex immune-fluorescence (mIF) determines the increase of CD163 + macrophage subsets in densities and reaches a 5.61-fold change 2 weeks after SBRT [ 40 ]. M1-type polarization is experimentally induced in vitro using exogenous toll-like receptor agonist, IFN- γ or combined with LPS, whereas the most potent M2-type is attained upon Th2 cytokine (like IL-4 and IL-13) stimuli [ 41 ].…”
Section: Macrophage Polarizationmentioning
confidence: 99%
“…Overall, a total of 13 studies were included in the final analysis: 3 for HFRT [ 9 , 10 , 11 ] and 10 for SBRT [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Only two studies reported on immune cell modification on TME [ 9 , 18 ], analyzing both biopsy tissues and pathological surgical specimens, while the 11 remaining studies analyzed peripheral blood sample [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 19 , 20 , 21 ]. Table 1 and Table 2 summarize all relevant details of these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, HDRT recruits many immune-suppressive cells such as MDSCs, Tregs, M2 macrophages, and cancer-associated fibroblasts (CAFs); causes the release of immune-suppressive factors; and dampens anti-tumor immunity [ 12 , 14 , 60 , 61 , 62 ]. M2 macrophages secrete immunosuppressive mediators such as IL-10 and TGF-β, inhibiting anti-tumor immunity and promoting a radioresistant phenotype [ 63 , 64 ].…”
Section: Immunobiology Mechanisms Of Hdrt + Ldrtmentioning
confidence: 99%
“…Furthermore, radiation, especially when the dose is high, has a cytotoxic effect on anti-tumor immune cells, which will impair anti-tumor immunity. Researchers have spent much effort on optimizing HDRT’s immune-stimulating effect and attenuating its negative immune effects [ 13 , 14 , 15 ]. Meanwhile, the evidence of the immune-modulating effect of low-dose RT (LDRT), defined as lower than 2 Gy/fraction, is also emerging [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation